(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study examined the extent to which cognitive strategy activators are represented in the official Arabic language textbook prescribed for sixth-grade primary school students among Palestinian learners from the 1948 territories within the Green Line, with particular attention to the formats through which these activators appear. A descriptive research approach, supported by descriptive statistical analysis was employed to achieve the study objectives. A curriculum content analysis instrument was developed to identify cognitive strategy activators according to four representational formats: symbolic, visual, auditory, and composite, the latter referring to integration across more than one format. In addition, qualitative analysis was used to interpret the findings and to support a critical discussion of the examined curricular reality, while also informing a future-oriented perspective for curriculum development. The findings revealed that cognitive strategy activators presented in a symbolic format were the most prevalent (0.63). Activators presented in a visual format ranked second (0.26), followed by composite activators (0.10), while activators presented in an auditory format were the least represented (0.02). Based on these findings, the study recommends that curriculum developers incorporate cognitive strategy activators across diverse representational formats in order to address variations in students’ learning styles and enhance the effectiveness of the teaching–learning process.